Experimental investigation and numerical simulation analysis of sintered micro-fluidic devices. (1st January 2020) - Barriere, T.; Sahli, M.; Agne, A.
ABSTRACT: This study investigates the use of numerical simulations to describe the solid-state diffusion of a sintering stage during a metal injection moulding process for micro-fluidic components with 316L stainless steel powders. Finite element (FE) analysis based on a thermo-elasto-viscoplastic model was conducted to describe the densification process of a stainless steel porous component during solid-state sintering. The numerical analyses, which were performed on a 3D micro-structured component with various powder volume loadings to take into account the thermal debinding effect to propose a full debinding sintering simulation, demonstrated that the FE simulation results are in agreement with the experimental ones.